Perspectives on abstract concepts cognition, language and communication - Bolognesi, Marianna; Steen, Gerard (Human cognitive processing (HCP) cognitive foundations of language structure and use,, 2019)
"Human language is the most powerful communication system that evolution has produced. Within this system, we can talk about things we can physically see, such as cats and tables, but also about more abstract entities, such as theories and feelings. But how are these abstract concepts grounded in human cognition and represented in the mind? How are they constructed in language? And how are they used in natural communication settings? This book addresses these questions through a collection of studies that relate to various theoretical frameworks, ranging from Conceptual Metaphor Theory to Words as Social Tools. Contributors investigate how abstract concepts are grounded in the mind, represented in language, and used in verbal discourse. This richness is matched by a range of methods used throughout the volume, from neuroimaging to computational modeling, and from behavioral experiments to corpus analyses"--